Galaktagogum in Local Vegetables: Habits Revealed by Science - Fadhilah, Nurul; Rahfiludin, Mohammad Zen; Lestantyo, Daru; Winarni, Sri (Global Health Science Group, 2024)
Breast milk has an ideal nutritional content for babies according to the needs to grow and develop optimally. Indonesia has a very rich diversity of foodstuffs, one of the habits of the Indonesian people is to regularly consume certain vegetables during breastfeeding. However, some vegetables are not yet popular for breastfeeding mothers to consume even though they contain many benefits such as banana heart, young papaya and spinach. The purpose of this literature review is to provide an evidence-based study on the potential of local vegetables that are commonly consumed during breastfeeding in Indonesia but the content of galaktogogum is not widely known, namely: papaya, spinach, and banana heart. This article is a literature review that discusses the potential of local plants as a source of galactogues. Article search involves 2 databases, namely PUBMED and Google Scholar. The keywords used are: (